Long-Term Patterns of Noise From Underwater Explosions and Their Relation to Fisheries in Southern California - Krumpel, Anna; Rice, Ally; Frasier, Kaitlin E.; Reese, Fairlie; Trickey, Jennifer S.; Simonis, Anne E.; Ryan, John P.; Wiggins, Sean M.; Denzinger, Annette; Schnitzler, Hans-Ulrich; Baumann-Pickering, Simone (Frontiers in Marine Science, 2021)
Acoustic deterrents can reduce marine mammal interactions with fisheries and aquacultures, but they contribute to an increasing level of underwater noise. In Southern California, commercially produced explosive deterrents, commonly known as “seal bombs”, are used to protect fishing gear and catch from pinniped predation, which can cause extensive economic losses for the fishing community. Passive acoustic monitoring data collected between 2005 and 2016 at multiple sites within the Southern California Bight and near Monterey Bay revealed high numbers of these small-charge underwater explosions, long-term, spatio-temporal patterns in their occurrence, and their relation to different commercial purse-seine fishing sectors. The vast majority of explosions occurred at nighttime and at many nearshore sites high explosion counts were detected, up to 2,800/day. Received sound exposure levels of up to 189 dB re 1 µPa2-s indicate the potential for negative effects on marine life, especially in combination with the persistence of recurring explosions during periods of peak occurrence. Due to the highly significant correlation and similar spatio-temporal patterns of market squid landings and explosion occurrence at many sites, we conclude that the majority of the recorded explosions come from seal bombs being used by the California market squid purse-seine fishery. Additionally, seal bomb use declined over the years of the study, potentially due to the reduced availability of market squid driven by a combination of warm water events in California and regulation enforcement. This study is the first to provide results on the distribution and origin of underwater explosions off Southern California, but there is a substantial need for further research on seal bomb use in more recent years and their effects on marine life, as well as for establishing environmental regulations on their use as a deterrent.